Perancangan Sistem Informasi Pendataan Kebijakan Pemerintah Pada Balai Syura Ureung Inong Aceh (BSUIA) - Agustina, Agustina (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2020)
Online media is a liaison, intermediary, and target as well as a communication tool channel to convey messages to the general public with planning and systematic and hopes to get a response from the recipient of the message, and of course, it requires a good response or response from the target audience. Therefore, it is necessary to design a media outreach that makes it easy for the public to get it or media that are easily accessible to the community, the form of an information media must be effective, easy to reach and in accordance with the habits and activities of the target audience, then the schedule for the distribution of the campaign media must be on time in accordance with needs. The purpose of this study was to design a Government Policy Data Collection Information System at the Ureung Inong Aceh Shura Center (BSUIA) based on PHP and MySQL. The method used in the Government Policy Data Collection Information System at the Ureung Inong Aceh Shura Hall (BSUIA) is to use the waterfall method or called the waterfall method. Data collection techniques using research methods by observation, interview, and literature study. The tools used are Adobe Dreamweaver and use web-based programming languages such as; PHP, MySQL, JavaScript JavaScript, JSON, JQuery as applications in interface design, and MySQL as DBMS. The test results of this application are the systems that are built already meet the needs, the input data process has met the needs and the resulting report has met the needs.